ISLAMIC SOCIAL REPORTING INDEX SEBAGAI INDIKATOR AKUNTABILITAS DAN TRANSPARANSI - Andi Ayu Frihatni; Darwis Said; Nadhirah Nagu; Widyantono Arif (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Islamic Social Reporting (ISR) is an interesting topic to discuss in shariaaccounting studies because so far the measurement of CSR disclosure in Shariahinstitutions mostly still refers to the Global Reporting Initiative Index. This indexis a reference for all types of companies in various countries regardless of shariaor non-Sharia aspects. This research aims to Identify the level of socialperformance of companies listed in JII by using content analysis by providing achecklist on each item that reveals social activities in the company's 2015 and2020 financial statements. The results of this study, found that in general thecompany has carried out the company's social responsibility well even thoughthere are still companies that in certain years do not do even minimally incarrying out their social responsibilities. No company has reached the fullfigure, namely the implementation and disclosure of the ISR Index on a 100%(one hundred percent) basis. This is due to the existence of sub-items of the ISRIndex that are impossible to meet by companies such as green products,environmental audits, and assistance for political activities.